Etika Hubungan Pendidik dan Peserta Didik menurut Perspektif Pendidikan Islam dan Pendidikan Barat (Studi Komparatif Pemikiran al-Zarnuji dan Paulo Freire) - Nur Salami; Anton Widyanto (DAYAH: Journal of Islamic Education, 2018)
The thoughts of al-Zarnuji and Paulo Freire are an interesting area to study since both have their respective advantages. Imam al-Zarnuji was a Muslim philosopher whose ideas are full of moral values, whereas Paulo Freire was a Western philoshopher whose ideas are full of liberation ideas in education, in which learners are led to actively engage with their own world. These two ideas are quite contrasting considering both came from totally different cultures, and thus studying their thoughts will certainly find a significant difference.